Determinants of Electricity Consumers Satisfaction in Selected Electricity Distribution Zones in Nigeria: Implications for Regulatory Activities - Usman, Abdullateef (Journal of Asian Business Strategy, 2013)
All over the world customers’ satisfaction has become a veritable tool for measuring organizational performance and relevance. This is the motivation for the investigation of determinant of consumers’ satisfaction in a service sector that has enjoyed state monopoly for a considerable length of time in Nigeria- the electricity sector. This paper therefore focused on the determinants of electricity consumers’ satisfaction in selected electricity distribution zone in Nigeria. To achieve the objective, the paper designs a scheme for evaluating customer’s satisfaction with a view to determine their level of satisfaction and in the process compute satisfaction index. The paper observed that consumers are at corner solution until the unbundling of the sector into DISCOs. It employed the Fussy Entropy to identify three classes of determinants of consumers’ satisfaction. The resulting indexes of consumers’ satisfaction shows that the consumers are not satisfied with the services of the DISCO. The paper concludes with policy recommendation to all stakeholders.